A new species of Asphinctopone (Hymenoptera: Formicidae: Ponerinae) from Tanzania - Hawkes, Peter G. (Zootaxa, 2010)
Asphinctopone is a rarely encountered genus of ponerine ants, previously known only from the wet forest zones of West and central Africa. In the most recent revision of the genus Bolton & Fisher synonymised the three previously described species under A. sylvestrii Santschi and described one new but very closely related species, A. differens Bolton & Fisher. A very distinctive new species, Asphinctopone pilosa sp. n., is described from Tanzania and represents the first record of this genus from East Africa. Modifications to the diagnosis of the genus and an updated key to the species of Asphinctopone are presented. An analysis of the distribution records of Asphinctopone, using BIOCLIM and DOMAIN as implemented in DIVA-GIS 7.1 to provide preliminary predictions of the potential range of the genus, is also provided.